Method for synthesizing octahedral nano cerium oxide with high Ce < 3 + > ratio and chemical mechanical polishing solution

By preparing octahedral nano cerium oxide with high Ce3+ ratio in chemical mechanical polishing, the problems of poor morphology control and poor polishing performance in the prior art are solved, and efficient polishing effect is achieved.

CN119409220APending Publication Date: 2025-02-11HUBEI SINOPHORUS ELECTRONIC MATERIALS CO LTD

Patent Information

Application Number
CN202411636088.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize octahedral nano cerium oxide with high Ce3+ ratio in chemical mechanical polishing, and its morphology control is poor, affecting the polishing performance.

Method used

By dissolving the organic ligand and cerium nitrate in deionized water, the ratio is controlled between 0.01-0.5:1:100-300, and stirring under a nitrogen atmosphere. Then, lye is added dropwise under a nitrogen atmosphere, and hydrothermal treatment is performed to control the reaction. The temperature is 80-150°C and the synthesis time is 6-8h. Centrifugation, drying and calcination are followed by preparation of octahedral nanocerium oxide with a high Ce3+ ratio.

Benefits of technology

The efficient preparation of octahedral nano cerium oxide with high Ce3+ ratio is achieved, with high chemical activity, uniform morphology and controllable particle size, which significantly improves the polishing rate and polishing accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409220A_ABST
    Figure CN119409220A_ABST
Patent Text Reader

Abstract

The invention provides a method for synthesizing octahedral nano cerium oxide with a high Ce < 3 + > ratio and a chemical mechanical polishing solution, the polishing solution takes the synthesized octahedral cerium oxide as a grinding material, and the octahedral cerium oxide is prepared by the following specific steps: dissolving a certain amount of organic ligand and cerous nitrate in deionized water; controlling the ratio of the organic ligand to cerous nitrate to water to be (0.01-0.5): 1: (100-300), and stirring for 1-2 hours in a nitrogen atmosphere; dropwise adding a certain amount of alkali liquor into the solution at a certain speed in a nitrogen atmosphere, carrying out hydrothermal treatment on the mixture, controlling the reaction temperature to be 80-150 DEG C and the synthesis time to be 6-8 hours, centrifuging, drying and calcining the mixture after the reaction, calcining at the calcining temperature to be 400-600 DEG C and calcining for 4-8 hours, thereby obtaining the catalyst. The particle size of the octahedral nano cerium oxide is about 30-50nm, and the Ce < 3 + > ratio of the octahedral nano cerium oxide is high. The polishing solution taking the octahedral nano cerium oxide prepared by the method as the abrasive material has good dispersity and stability, high polishing rate and low surface roughness, and has wide popularization and application values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation and relates to a high Ce 3+ A method for preparing octahedral nano-cerium oxide with a high ratio. Background Art

[0002] Integrated circuit technology has developed rapidly with the improvement of information technology. As the integration level increases, the feature size decreases, resulting in a three-dimensional structure and multi-layer wiring, which requires the surface between the layers inside the integrated circuit to have a high degree of flatness. Chemical mechanical polishing is currently the most widely used flattening technology. The main consumables in this process are polishing liquid and polishing pads. Polishing liquid is also one of the main factors affecting the performance of chemical mechanical polishing. The composition of the polishing liquid includes abrasives, various chemical additives and water. Among them, abrasives have the highest cost and are mostly monopolized by foreign countries.

[0003] Cerium dioxide is an important rare earth oxide with suitable hardness. 3+ and Ce 4+ Because of the presence of oxygen vacancies, they can be converted into each other, making it chemically active and can be used as an abrasive in chemical mechanical polishing, as well as in air purification and solid fuel cells. 2 The performance of CeO2 is strongly affected by its morphology, particle size and exposed crystal surface. There are many methods for preparing nano CeO2, including microemulsion method, sol-gel method, electrolytic deposition method, metal salt hydrolysis method, hydrothermal method and microwave method. 2 It has been successfully synthesized, such as nanocubes, octahedrons, nanorods, nanotubes, nanosheets, etc. Compared with other shapes of cerium dioxide nanocrystals, CeO 2 , exposing the most stable (111) crystal plane, containing more oxygen vacancies and Ce 3+ , has higher chemical activity and can achieve higher polishing rate when applied.

[0004] Patent CN105480999A discloses a method for preparing hierarchical nanostructured cerium oxide octahedrons. A certain amount of alkali is added to a mixed solution of cerium nitrate and polyvinyl pyrrolidone, and a hydrothermal reaction is carried out at a certain temperature to obtain hierarchical nanostructured cerium oxide octahedrons. However, this method has a long synthesis time and a high reaction temperature, and is difficult to promote industrially. Patent CN116285700A discloses a method for preparing a high Ce 3+ Nano-cerium oxide polishing liquid and its preparation method and its application in gallium arsenide polishing are prepared by adding an organic alkali solution containing a dispersant to a mixed solution of chloroalkane, 4-vinylpyridine and cerium salt, and controlling the pH value of the reaction to obtain a high Ce oxide with a primary particle size of 20-50nm.3+ The nano-cerium oxide has a ratio of 1.5 to 2.5 and has angular corners, but its morphology is poorly controlled. Therefore, a nano-cerium oxide with an octahedral morphology and Ce 3+ Cerium oxide with high specific gravity is of great significance as an abrasive for chemical mechanical polishing. Summary of the invention

[0005] The present invention proposes a method for synthesizing high Ce 3+ A method for preparing octahedral nano-cerium oxide with high ratio and a chemical mechanical polishing liquid.

[0006] The preparation method of the present invention comprises the following steps: (1) dissolving a certain amount of organic ligand and cerium nitrate in deionized water, controlling the ratio of organic ligand, cerium nitrate and deionized water to be 0.01-0.5:1:100-300, and stirring for 1-2 hours under a nitrogen atmosphere; (2) adding a certain amount of alkali solution to the solution of step (1) at a certain speed under a nitrogen atmosphere; (3) Under a nitrogen atmosphere, the mixture is subjected to hydrothermal treatment, the reaction temperature is controlled between 80-150°C, the synthesis time is 6-8h, and after the reaction, the mixture is centrifuged, dried and calcined at a calcination temperature of 400-600°C for 4-8h.

[0007] Preferably, the organic ligand is a biligand selected from one or more of biphenyl dicarboxylic acid, 2,2-bipyridine-5,5-dicarboxylic acid, trimesic acid, 2-aminoterephthalic acid, benzoic acid, salicylic acid, 1,2,4-benzenetricarboxylic acid, 4-vinylpyridine, 4-dimethylaminopyridine, diaminopyridine, and 3-methylpyridine.

[0008] Preferably, one organic ligand of the dual ligand is a carboxylic acid substance with a benzene ring, and the other organic ligand is a pyridine substance, and the molar ratio thereof is controlled between 1:1 and 1:3.

[0009] Preferably, the ratio of the organic ligand, cerium nitrate and deionized water is controlled between 0.1-0.5:1:150-300.

[0010] Preferably, the alkali solution is a certain amount of alkali dissolved in deionized water, and the alkali is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, piperazine, 2-aminopiperazine, triethanolamine, ethylenediamine, 1,2-propylenediamine, butylamine, propylamine, diethylenetriamine, triethylenetetramine, monoethanolamine, etc.

[0011] Preferably, in the alkali solution, the ratio of alkali to deionized water is controlled between 0.05-0.5:1.

[0012] Preferably, the dropping speed of the alkali solution is controlled between 1-10 mL / min, and the dropping is completed during the stirring process.

[0013] The present invention also provides a high Ce 3+ The octahedral nano-cerium oxide is prepared by using the method for synthesizing octahedral nano-cerium oxide, wherein Ce 3+ / Ce 4+ The ratio is 0.3 or more, and more preferably Ce 3+ / Ce 4+ The ratio is 0.4 or more, and more preferably Ce 3+ / Ce 4+ The ratio is 0.5 or more.

[0014] The morphology of the cerium oxide synthesized above is octahedral. 3+ / Ce 4+ It has a large ratio, high lattice oxygen content, high chemical activity, controllable particle size, and uniform morphology, and can achieve higher polishing rate and polishing accuracy when used.

[0015] The preparation method of the chemical mechanical polishing liquid is as follows: 3+ Octahedral cerium oxide, organic acid and part of dispersant are added into water and dispersed by high pressure homogenizer so that the particle size D50 is controlled at about 100 nm. Then the remaining components are added and stirred to obtain polishing liquid.

[0016] The chemical mechanical polishing liquid is applied in a silicon carbide substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the SEM image of the product obtained in Example 1.

[0018] Figure 2 This is the TEM image of the product obtained in Example 1.

[0019] Figure 3 This is the TEM image of the product obtained in Example 2.

[0020] Figure 4 This is the TEM image of the product obtained in Example 3.

[0021] Figure 5 This is the TEM image of the product obtained in Example 4.

[0022] Figure 6 This is the TEM image of the product obtained in Example 5.

[0023] Figure 7 This is the TEM image of the product obtained in Comparative Example 1.

[0024] Figure 8 This is the TEM image of the product obtained in Comparative Example 1. DETAILED DESCRIPTION

[0025] The advantages of the present invention are further described below through specific examples, but the protection scope of the present invention is not limited to the following examples.

[0026] Example 1 Weigh 0.42g of trimesic acid, 0.21g of 4-vinylpyridine and 4.34g of cerium nitrate, dissolve in 30g of deionized water, and stir for 1h under nitrogen atmosphere; mix 6.84g of ammonia water with 18.5g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, inject ammonia solution into the cerium salt mixture at 5mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 100℃, and the synthesis time at 6h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. 3+ The ratio of nano octahedral cerium oxide, such as the attached Figure 1 As shown in SEM, when the TEM is photographed, the octahedron is projected and appears as a hexagon. The particle size is 30nm, as shown in the attached Figure 2 shown.

[0027] Example 2 Weigh 0.122g of benzoic acid, 0.093g of 3-methylpyridine and 4.34g of cerium nitrate, dissolve in 30g of deionized water, and stir for 1h under nitrogen atmosphere; mix 3.05g of monoethanolamine with 18g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, and then inject the monoethanolamine solution into the cerium salt mixture at 10mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 85℃, and the synthesis time at 6h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. 3+ The nano-octahedral cerium oxide has a particle size of 25 nm as shown in the attached Figure 3 shown.

[0028] Example 3 Weigh 0.484g of biphenyl dicarboxylic acid, 0.279g of 3-methylpyridine and 8.68g of cerium nitrate, dissolve in 80g of deionized water, and stir for 1h under nitrogen atmosphere; mix 10g of sodium hydroxide with 18g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, and then inject the sodium hydroxide solution into the cerium salt mixture at 10mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 90℃, and the synthesis time at 8h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. 3+ The nano-octahedral cerium oxide has a particle size of 35 nm as shown in the attached Figure 4 shown.

[0029] Example 4 Weigh 0.362g of 2-aminoterephthalic acid, 0.315g of 4-vinylpyridine and 8.68g of cerium nitrate, dissolve in 55g of deionized water, and stir for 2h under nitrogen atmosphere; mix 9.05g of tetramethylammonium hydroxide with 18g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, and then inject TMAH solution into the cerium salt mixture at 5mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 100℃, and the synthesis time at 8h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. 3+ The nano-octahedral cerium oxide has a particle size of 50 nm as shown in the attached Figure 5 shown.

[0030] Example 5 Weigh 0.3453g of salicylic acid, 0.916g of 4-dimethylaminopyridine and 8.68g of cerium nitrate, dissolve in 80g of deionized water, and stir for 1h under nitrogen atmosphere; mix 6.84g of ammonia water with 36g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, and then inject the ammonia solution into the cerium salt mixture at 8mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 100℃, and the synthesis time at 6h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. 3+ The nano-octahedral cerium oxide has a particle size of 30 nm as shown in the attached Figure 6 shown.

[0031] Comparative Example 1 Weigh 0.42g of trimesic acid and 4.34g of cerium nitrate, dissolve in 30g of deionized water, and stir for 1h under nitrogen atmosphere; mix 6.84g of ammonia water with 18.5g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, and inject ammonia solution into the cerium salt mixture at 5mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 100℃, and the synthesis time at 6h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. Amorphous nano-cerium oxide is obtained, and TEM shows as shown in the attached figure. Figure 7 .

[0032] Comparative Example 2 Weigh 0.315g of 4-vinylpyridine and 8.68g of cerium nitrate, dissolve in 55g of deionized water, and stir for 2h under nitrogen atmosphere; mix 9.05g of tetramethylammonium hydroxide with 18g of deionized water, stir for 0.5h under nitrogen atmosphere after mixing, and then inject TMAH solution into the cerium salt mixture at 5mL / min; hydrothermally treat the mixture under nitrogen atmosphere, control the reaction temperature at 100℃, and the synthesis time at 8h. After the reaction, centrifuge, dry and calcine the mixture at 600℃, increase the temperature at 2℃ / min, and calcine for 4h. Multi-rod-shaped nano-cerium oxide is obtained, and TEM shows as shown in the attached figure. Figure 8 shown.

[0033] In order to further characterize the use of high Ce in the present invention 3+ In the case of octahedral cerium oxide, the high Ce in the above Examples 1-5 and Comparative Examples 1-2 is used. 3+ The chemical mechanical polishing liquid was prepared by using octahedral cerium oxide with a ratio of 1:1 to 1:1, and the polishing rate of the polishing liquid on the silicon carbide wafer was further measured. The specific test conditions are as follows: The nano-cerium oxide prepared in Examples 1-5 and Comparative Examples 1-2 contains 1 wt% of the dispersion, and the system pH is adjusted to about 3 (using 1% dilute nitric acid as a pH regulator). The polishing removal rate (RR) of each group of polishing liquids on the silicon surface of the silicon carbide wafer is evaluated under different test pressures. The polishing conditions are: the polishing machine is a Fangda grinder, the Sbua800 polishing pad, the upper and lower disc speeds are both 50 rpm, the pressure is 7.5 psi, the polishing liquid flow rate is 50 mL / min, and the polishing time is 30 min.

[0034]

[0035] According to the above experimental results, the high Ce synthesized in the present invention 3+ The comparison between Example 1 and Comparative Example 1, and between Example 2 and Comparative Example 2, shows that Ce3+ / Ce 4+ Octahedral cerium oxide with a large ratio and regular morphology can significantly increase the polishing rate of the polishing liquid on the wafer.

[0036] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A synthetic high Ce 3+ The method for producing octahedral nano-cerium oxide is characterized in that: The synthesized octahedral cerium oxide is used as an abrasive, and the preparation of the octahedral cerium oxide is as follows: (1) dissolving a certain amount of organic ligand and cerium nitrate in water, controlling the ratio of organic ligand, cerium nitrate and water to be 0.01-0.5:1:100-300, and stirring for 1-2 hours under a nitrogen atmosphere; (2) adding a certain amount of alkali solution to the solution of step (1) at a certain speed under a nitrogen atmosphere; (3) Under a nitrogen atmosphere, the mixture is subjected to hydrothermal treatment, the reaction temperature is controlled between 80-150°C, the synthesis time is 6-8h, and after the reaction, the mixture is centrifuged, dried and calcined at a calcination temperature of 400-600°C for 4-8h.

2. A synthetic high Ce according to claim 1 3+ The method for producing octahedral nano-cerium oxide is characterized by: The organic ligand described in step (1) is a biligand, and the biligand is selected from one or more of biphenyl dicarboxylic acid, 2,2-bipyridine-5,5-dicarboxylic acid, trimesic acid, 2-aminoterephthalic acid, benzoic acid, salicylic acid, 1,2,4-benzenetricarboxylic acid, 4-vinylpyridine, 4-dimethylaminopyridine, diaminopyridine, and 3-methylpyridine.

3. A synthetic high Ce according to claim 2 3+ The method for producing octahedral nano-cerium oxide is characterized by: One organic ligand in the dual ligand is a carboxylic acid substance with a benzene ring, and the other organic ligand is a pyridine substance, and the molar ratio thereof is controlled between 1:1 and 1:

3.

4. A synthetic high Ce according to claim 1 3+ The method for producing octahedral nano-cerium oxide is characterized by: The ratio of the organic ligand, cerium nitrate and deionized water in step (1) is controlled within the range of 0.01-0.5:1:100-300, preferably within the range of 0.1-0.5:1:150-300.

5. A synthetic high Ce according to claim 1 3+ The method for producing octahedral nano-cerium oxide is characterized by: The alkali solution in step (2) is prepared by dissolving a certain amount of alkali in deionized water, wherein the alkali is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, piperazine, 2-aminopiperazine, triethanolamine, ethylenediamine, 1,2-propylenediamine, butylamine, propylamine, diethylenetriamine, triethylenetetramine, monoethanolamine, etc.

6. A synthetic high Ce according to claim 1 3+ The method for producing octahedral nano-cerium oxide is characterized by: In the alkali solution described in step (2), the ratio of alkali to deionized water is controlled between 0.05-0.5:

1.

7. A synthetic high Ce according to claim 1 3+ The method for producing octahedral nano-cerium oxide is characterized by: The dropping speed in step (2) is controlled between 1-10 mL / min, and the dropping is completed during the stirring process.

8. A high Ce 3+ Octahedral nano-cerium oxide, characterized in that: The method for synthesizing octahedral nano-cerium oxide according to any one of claims 1 to 7 is used, wherein Ce 3+ / Ce 4+ The ratio is 0.3 or more.

9. A chemical mechanical polishing liquid, characterized in that: It comprises the octahedral nano cerium oxide as described in claim 8.

Citation Information

Patent Citations

  • Preparation method of multilevel-structure nano cerium oxide octahedron

    CN105480999A

Cited By

  • Composite material as well as preparation method and application thereof

    CN120057972A

  • Preparation method of hydroxyapatite-cerium oxide composite material and chemical mechanical polishing solution

    CN121651303A

  • Octahedral cerium oxide as well as preparation method and application thereof

    CN122035923A